THE INFLUENCE OF ORGANIZATIONAL COMMITMENT ON PERFORMANCE WITH ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) AS MEDIATION FOLLOWING THE IMPLEMENTATION OF THE MERDEKA CURRICULUM - Novi Fitria Hermiati; Pupung Purnamasari; Yunita Ramadhani RDS (SEAN Institute, 2022)
This study aims to determine the influence between organizational commitment and organizational citizenship behavior (OCB) as an intervening variable in the implementation of an independent curriculum (Empirical Study on Kindergarten Teachers). The type of research used is a quantitative approach. The instrument used is a questionnaire with multiple choice options that must be selected from 5 choices. The population in this study was all educators who were in kindergarten institutions in Bekasi City. The purposive sampling technique is a sampling technique in this study, where in choosing the sample according to what the researcher expects and can represent characteristics in the population. The results obtained state that the evaluation of measurements has good validity through the Average Varian Extracted measurement model and means that all constructs meet the criteria for the validity of discrimination.